Penerapan Strategi Gallery of Learning dalam Meningkatkan Hasil Belajar IPA - Pattimura, Hairani; Natsir, Nur Alim (COGNITIVISM: Journal of Educational Research and Development, 2025)
This study aims to determine the application of the gallery of learning strategy in improving science learning outcomes in the concept of the respiratory system of grade V students of SD Al-Hillal2 Ambon. The type of research used is Classroom Action Research and consists of four stages, namely planning, action, observation, and reflection. The number of subjects is 25 people. The instruments used are tests and observation sheets. Tests are used to determine student learning outcomes and observations are used to determine student activities in learning through the Gallery of Learning strategy. The data analysis was used descriptively. The results of the analysis show that the application of the Gallery of Learning learning strategy in studying respiratory system material in humans can improve student learning outcomes in grade V of SD Al-Hillal 2 Ambon.  This result is shown based on the test results obtained by students, namely in the initial test it shows that of the 25 students who are the subjects in this study, only 3 students completed with a percentage of 12.00%. In the first cycle, the percentage of student learning completeness reached 52.00%, in the second cycle, the percentage of student learning completeness reached 100%. Thus, the percentage of completeness has reached classical completeness, namely 75%.